Involvement of trade unions to supervision and control of legislation on labor maintenance in the period of establishment in Ukraine in 1917–1921 - Галина Василівна Терела (Проблеми Законності, 2017)
In the article, on the basis of the conducted analysis of the resolutions, instructions, subtitles of the People's Commissariat of Labor of the UkrSSR, the memoranda of the local departments of labor as well-known and for the first time discovered in the archival funds, it was determined that the factory and plant committees and local service committees, being primary centers of All-Russian Central Council of Trade Unions, served as a low authority to legislation on labor legislation maintenance. For this purpose, under the factory committees and trade unions permanent commissions were established for labor protection. The order of the involvement of trade unions to the election of labor (legal), out of district and sanitary labor inspectors, controllers of the People's Committee of state control is analyzed. It was clarified that in practice the involvement of trade unions in the activity of supervision and control bodies in the field of labor was not as active as it was decreed, and was partially replaced by the party representation.